I am the traitor - Zadoff, Allen (Zadoff, Allen. Unknown assassin, 2015)
After breaking free of The Program, Boy Nobody is on a mission of his own to reclaim his life and rescue his friend Howard from the secret organization that has turned him and other orphaned children into trained assassins--but he has no idea who, if anyone, he can trust, or what the consequences will be if he succeeds in bringing down The Program.